Peningkatan Kemandirian Operasional Tempat Ibadah Melalui Usaha Dharma Coffee dan Roastery Pada Umat Buddha di Kabupaten Temanggung - Walyono, Walyono; Hariyanto, Hariyanto; Sukarti, Sukarti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Vihara has a very strategic role in society. Its roles are very diverse, in addition to being a place to seek inner peace or happiness and a place of worship to unify society to anticipate turmoil and a new social order. The purpose of community service is to explore the potential of Dharmaguna Avalokitesvara Vihara. Aims to increase the independence of temple operational costs through the Coffee roasting business. Method: The community service method uses the ABCD Asset-based community development approach at Dharmaguna Avalokitesvara Vihara. Result: The result of the dedication is education about modern Coffee processing, namely Coffee roasting processing, which can help temples and surrounding residents get better prices. The benefits received by the people and surrounding residents, as well as the general public, also benefit economically because the raw materials for Dharma café and Roastery are obtained from local residents. Conclusion: In addition, residents can also taste good quality Coffee from their own production. People and youth participate both as suppliers of production materials and participate in advertising Dharma Caffe and Roastery products as resellers.